Subliminal affective priming in clinical depression and comorbid anxiety: A longitudinal investigation - Dannlowski, Udo; Kersting, Anette; Lalee-Mentzel, Judith; Donges, Uta-Susan; Arolt, Volker; Suslow, Thomas (Psychiatry research, 2006)
In the present study, the sequential affective priming paradigm developed by Fazio et al. [Fazio, R.H., Sanbonmatsu, D.M., Powell, M.C., Kardes, F.R., 1986. On the automatic activation of attitudes. Journal of Personality and Social Psychology 50, 229–238.] was applied for the first time to investigate automatic cognitive bias in depressed patients. Unipolar depressed patients ( n = 22) were tested on admission and after about 7 weeks of inpatient psychotherapy. Half of the patients ( n = 11) were suffering from a comorbid anxiety disorder. Twenty-two healthy subjects served as controls. Affectively polarized prime words were presented subliminally followed by positive or negative target words, which had to be evaluated. Subjects' affective state was assessed by self-report measures. In the course of psychotherapy, patients recovered significantly. Study groups exhibited qualitatively different affective priming effects: In non-comorbid depressed patients, no affective priming was found. Instead, a highly significant main effect of prime valence emerged, indicating a Stroop-like interference of negative prime words at time 1. This negative bias was associated with depression level at time 1 and could not be found after recovery. Affective priming was observed in controls and comorbid patients, but in opposite directions. Direction and strength of affective priming was directly associated with anxiety level at both times. The affective priming paradigm provides evidence for differential group effects regarding unconscious emotional information processing.